A new method to access triazole-fused spiro-guanidines from the reaction of isothiocyanates tethered N-sulfonyl-1, 2, 3-triazoles and amines. Issue 11 (7th September 2016) - Liu, Hou-Lu; Jiang, Yu; Hao, Jian; Tang, Xiang-Ying; Shi, Min
Abstract : The reaction of isothiocyanate tethered N -sulfonyl-1, 2, 3-triazoles and amines afforded asymmetrical guanidines in fair to excellent yields through a two-component tandem reaction process. Abstract : A novel method to access triazole-fused spiro-guanidine from the reaction of isothiocyanate tethered N -sulfonyl-1, 2, 3-triazoles and amine has been developed. The reactions proceeded through a two-component tandem reaction, including nucleophilic addition, base-assisted intramolecular (or intermolecular) nucleophilic substitution and subsequent intramolecular nucleophilic addition–elimination process. A wide range of protected oxindole skeletons and amines are well-tolerated.